2008
DOI: 10.1073/pnas.0806335105
|View full text |Cite
|
Sign up to set email alerts
|

The CD83 reporter mouse elucidates the activity of the CD83 promoter in B, T, and dendritic cell populationsin vivo

Abstract: CD83 is the major surface marker identifying mature dendritic cells (DCs). In this study, we report the generation of reporter mice expressing EGFP under the control of the CD83 promoter. We have used these mice to characterize CD83 expression by various immune system cell types both in vivo and ex vivo and under steady-state conditions and in response to stimulation with a Toll-like receptor (TLR) ligand. With those mice we could prove in vivo that the CD83 promoter is highly active in all DCs and B cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Furthermore the engagement of the BCR of BCR-transgenic (tg) B cells with cognate antigen (Ag) in vivo results in a strong induction of CD83 [7]. In line with these findings a CD83 reporter mouse reveals a highly activated CD83 promoter in murine B cells [22].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore the engagement of the BCR of BCR-transgenic (tg) B cells with cognate antigen (Ag) in vivo results in a strong induction of CD83 [7]. In line with these findings a CD83 reporter mouse reveals a highly activated CD83 promoter in murine B cells [22].…”
Section: Introductionmentioning
confidence: 82%
“…CD83 expression is rapidly induced on the surface of B cells activated by TLR-engagement through LPS or BCR-ligation by application of an anti-BCR mAb in vitro or by application of the cognate Ag in BCRtg systems in vivo [5][6][7]. The CD83 promoter per se is highly active in B cells [22] and CD83 exhibits a similar expression kinetic as the likewise activation induced costimulatory molecules CD80 and CD86 [7]. CD83 occurs on the surface of activated B cells in vitro [6] and in vivo [7] prior to the early activation marker CD69.…”
Section: Discussionmentioning
confidence: 99%
“…CD83, however, is also expressed by many activated murine leukocytes, such as DC (5,7,39), T effector cells (9,20), regulatory T cells (10), TEC (16), and the periarteriolar lymphoid sheath in the white pulp (7). It is, therefore, likely that anti-CD83 mAb, upon injection, would bind to all of these CD83-positive cell types and tissues in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was corroborated by the analysis of CD83-deficient mice, which had a specific block in CD4 ϩ single-positive thymocyte development [54]. Recent in vivo analysis using transgenic mice revealed that cell surface expression of CD83 is mainly controlled by posttranscriptional regulation [55]. CD83 is costimulatory for human T cells [56].…”
Section: Cd83mentioning
confidence: 89%